Gestión de recursos web para la difusión de los beneficios de la organización Unorico Samashunchic. - Naranjo, Fredy R. (2020)
After a diagnosis about the means of communication used by the organization Unorico Samashunchik, three accounts were registered in different social networks such as facebook, instagram and youtube for the dissemination of information about and the organization as well as the benefits it offers. Subsequently made the design of a web page with elements that identify the organization In addition to basic information about it, opening hours, services and a form to request more information. Using some web resources, designed and published videos, posters, photographs and advertisements in the three social networks of the organization. Finally, the username and password data were delivered to the representatives and a live videoconference was held through Facebook live of the organization for the dissemination of its benefits.